IMF effect on sporadic-E layers at two northern polar cap sites: Part II – Electric field - T. Nygrén; A. T. Aikio; M. Voiculescu; J. M. Ruohoniemi (Annales Geophysicae, 2006)
This paper is the second in a series on a study of the link between IMF and sporadic-E layers within the polar cap. In PaperI (Voiculescu et al., 2006), an analysis of the sporadic-E data from Thule and Longyearbyen was presented. Here we concentrate on the electric field mechanism of sporadic-E generation. By means of model calculations we show that the mechanism is effective even at Thule, where the direction of the geomagnetic field departs from vertical only by 4. The model calculations also lead to a revision of the electric field theory. Previously, a thin layer was assumed to grow at a convergent null in the vertical ion velocity, which is formed when the electric field points in the NW sector. Our calculations indicate that in the dynamic process of vertical plasma compression, a layer is generated at altitudes of high vertical convergence rather than at a null. Consequently, the layer generation is less sensitive than previously assumed to fluctuations of the electric field direction within the NW sector. The observed diurnal variations of sporadic-E occurrence at Longyearbyen and Thule are compared with the diurnal variations of the electric field, calculated using a representative range of IMF values by means of the statistical APL model. The results indicate that the main features of Es occurrence can be explained by the convection pattern controlled by the IMF. Electric fields calculated from the IMF observations are also used for producing distributions of sporadic-E occurrence as a function of electric field direction at the two sites. A marked difference between the distributions at Thule and Longyearbyen is found. A model estimate of the occurrence probability as a function of electric field direction is developed and a reasonable agreement between the model and the experimental occurrence is found. The calculation explains the differences between the distributions at the two sites in terms of the polar cap convection pattern. The conclusion is that the electric field is the major cause for ...